Partnering to Improve Mentorship Capacity for Ugandan Reproductive Health Researchers: Program Description and Evaluation - Julie M. Buser; Ella August; Faelan E. Jacobson-Davies; Felix Bongomin; Edward Kumakech; Rachel Gray; Pebalo Francis Pebolo; Anna Grace Auma; Tamrat Endale (The American Journal of Tropical Medicine and Hygiene, 2023)
Mentorship is essential to health researchers in achieving their full potential and advancing public health. In most low-resource settings, there is a paucity of training on how to be a successful mentor. The Center for International Reproductive Health Training at the University of Michigan conducted and evaluated a workshop at two universities in Uganda for mentors of new reproductive health research grant awardees. The program aimed to strengthen mentors’ mentorship skills and to identify ways to foster institutional support for mentoring. Mentors rated their post-training skills using a 5-point Likert scale (not skilled to extremely skilled) immediately and 3 months after the training. Ten of 19 mentors who participated in the training completed the evaluation. The majority were 41 to 50 years old, male, midcareer faculty. Immediately after the training, mentors rated themselves (mean ± SD) highest in knowledge of research ethics (4.4 ± 0.5), fostering independence in mentees (4.3 ± 0.9), and understanding the benefits of mentoring (3.9 ± 1.1). Mentors felt least confident in fostering institutional change to support mentorship (3.3 ± 0.8), communication (3.5 ± 0.5), and overcoming adversity (3.5 ± 0.8). The two most important things the mentors learned were how to appreciate and manage diversity and how they can benefit from mentorship. Barriers to mentoring that persisted after the program ended included lack of time and institutional resources. Enhancing mentorship training opportunities will foster a generation of scientists who are more supported, skilled, and productive in research, leading to better reproductive and public health outcomes in their communities.